A novel octanuclear nickel(II)–molybdenum(VI) heterometallic cluster based on the salicylhydroxamate ligand. Issue 2 (26th January 2016) - Dou, Ming-Yu; Lu, Jing
Abstract : Salicylhydroxamic acid is known for its strong coordination ability and multiple coordination modes. In a structure based on the salicylhydroxamate ligand, salicylhydroxamate(3−), acetate, hydroxide and oxide ligands adopt complicated coordination modes and link six Ni II and two Mo VI cations into an octanuclear heterometallic cluster. Studies of the magnetic properties reveal antiferromagnetic interactions between the Ni II cations. Abstract : Salicylhydroxamic acid (H3 shi) is known for its strong coordination ability and multiple coordination modes, and can easily coordinate to metal cations to form compounds with five‐ or six‐membered rings, as well as mono‐, di‐ and multinuclear compounds with interesting structures having potential applications in organic chemistry, coordination chemistry, and the materials and biological sciences. A novel octanuclear nickel(II)–molybdenum(VI) heterometallic cluster based on the salicylhydroxamate ligand, namely di‐μ3 ‐acetato‐di‐μ2 ‐acetato‐di‐μ3 ‐hydroxido‐di‐μ3 ‐oxido‐tetraoxidooctakis(pyridine‐κ N )bis(μ5 ‐salicylhydroxamato)hexanickel(II)dimolybdenum(VI) monohydrate, [Mo2 Ni6 (C7 H4 NO3 )2 (C2 H3 O2 )4 O5 (OH)2 (C5 H5 N)8 ]·H2 O, (I), was synthesized by the reaction of sodium molybdate, nickel acetate and salicylhydroxamic acid in a dimethylformamide/pyridine/methanol solution at room temperature. The salicylhydroxamate(3−) (shi 3− ), acetate and oxide ligands adopt complicated coordination modes and link six Ni II and two Mo VI cations into the octanuclear heterometallic cluster. All of the metal cations exhibit octahedral coordination geometries and are connected to each other through the sharing of corners, edges or planes. The heterometallic clusters are further connected to form two‐dimensional supramolecular layers through weak C—H…O hydrogen bonds. Studies of the magnetic properties of the title compound reveal antiferromagnetic interactions between the Ni II cations.